SUD-KIMYO LABORATORIYASI TEKSHIRUVLARI UCHUN FUQAROLARDAN QON VA SIYDIK OLISH TARTIBI - Ismailova Lazzat Nurjon qizi; Odilova Shoxsanam Axrorxo’ja qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Аннотaция: Надлежащий сбор образцов крови и мочи у граждан в соответствии с законами и правилами обеспечивает точность экспертных исследований и предоставление правдивых выводов. Annotation: Proper collection of blood and urine samples from citizens in accordance with laws and regulations ensures the accuracy of expert examinations and the provision of truthful conclusions.